Sistem pendukung keputusan pemilihan tanaman pangan berbasis web dengan Fuzzy Weighted Product - Aldegunda Naisali; Yoseph Pius Kurniawan Kelen; Risald Syarifuddin; Dian Grace Ludji (Universitas Trunojoyo Madura, 2025)
The selection of food crops in North Central Timor Regency is based on individual experience and unstructured and unsystematic information. This process is subjective, depending on the experience or habits of farmers without the support of objective data analysis. This makes decision-making in determining the type of food crop less precise, and can hinder agricultural productivity. This study aims to build a web-based decision support system (DSS) that helps select the most appropriate food crops based on various criteria and alternatives. The system is developed using the Fuzzy Multi Attribute Decision Making (FMADM) and Weighted Product (WP) methods that handle uncertainty in evaluation and weighting. Fuzzy is used to accommodate linguistic qualitative data such as “sufficient”, “good”, or “very good”, reflecting real conditions in the field. Meanwhile, the Weighted Product method calculates the final score of each crop alternative based on the attribute value and weight of each criterion. The criteria in this system include planting area, harvested area, productivity, production, soil type, and market demand. This study aims to develop a web-based decision support system that provides recommendations for selecting the best food crops. This system is designed with an easy-to-use interface, and can be accessed online by farmers, extension workers, and policy makers. In this system, a fuzzy and weighted product approach is used to manage uncertainty in the assessment and produce objective crop rankings. The implementation results show that lowland rice plants get the highest score, which is 0.232977225 compared to other alternatives. This value indicates the highest level of feasibility of all the alternative crops analyzed, so lowland rice is the most recommended choice. This system is able to provide fast, data-based recommendations.Keywords: Fuzzy, Decision Support System, Food Crops, Weighted product, Web